2010
DOI: 10.3390/ijms11114488
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Whole Human Saliva Detects Enhanced Expression of Interleukin-1 Receptor Antagonist, Thioredoxin and Lipocalin-1 in Cigarette Smokers Compared to Non-Smokers

Abstract: A gel-based proteomics approach was used to screen for proteins of differential abundance between the saliva of smokers and those who had never smoked. Subjecting precipitated proteins from whole human saliva of healthy non-smokers to two-dimensional electrophoresis (2-DE) generated typical profiles comprising more than 50 proteins. While 35 of the proteins were previously established by other researchers, an additional 22 proteins were detected in the 2-DE saliva protein profiles generated in the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
5
25
1
Order By: Relevance
“…Our verified salivary biomarkers also have been reported to be related with smoking (5,6). References show that the three verified biomarkers also related with COPD in tissue (37), bronchoalveolar lavage fluids (46), and blood (16,47).…”
Section: Fig 5 Performance Of Biomarker Panelmentioning
confidence: 82%
See 2 more Smart Citations
“…Our verified salivary biomarkers also have been reported to be related with smoking (5,6). References show that the three verified biomarkers also related with COPD in tissue (37), bronchoalveolar lavage fluids (46), and blood (16,47).…”
Section: Fig 5 Performance Of Biomarker Panelmentioning
confidence: 82%
“…Small cell lung cancer (SCLC) is another type of lung cancer, which represents about 15% of cases (3). Cigarette smoking causes lung cancer, which is by far the major risk factor (4,5,6). Lung cancer has a high mortality rate among malignancies, in part because symptoms are frequently absent until disease is already metastatic and is, therefore, incurable (7,8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper four S100A9 protein species have been characterized in the acid-soluble fraction of preterm newborn saliva by HPLC-ESI-MS/MS analysis: two protein species (long-type), acetylated at the N-terminus, differing for the presence of a phosphate group on Thr 112 , and two other protein species lacking the TCKM amino peptide (short-type), also acetylated at the N-terminus and differing for the presence of a phosphate group on Thr 108 [8]. In several 2-DE analyses of adult whole saliva, S100A9 has been identified in different spots, but up to now the correspondence among spots and PTMs has never been elucidated [15,17]. In the present study S100A9 has been identified (Table 2) in four spots (1A, 1B, 2 and 11) of 2-DE gel from the acid-insoluble fraction of preterm newborn ( Fig.…”
Section: S100 Familymentioning
confidence: 97%
“…Positive skin prick tests were obtained from his saliva in this patient, but the saliva extract did not cause a reaction in normal, non-allergic subjects. There is also the question of whether the cigarette smoking might have enhanced the allergenic activity of the salivary proteins [10] and whether there was any periodontal disease in the partner which might have influenced histamine levels in the partner's saliva in combination with the cigarette smoking [11]. The inability to follow this case further is disappointing, but the case does raise some interesting future directions of study.…”
Section: Journ a L O F A Llergy And T H E Ra Py Issn: 2155-6121mentioning
confidence: 99%